Dynamic CO Adsorption and Desorption through the Ionic Liquid Layer of a Pt Model Solid Catalyst with Ionic Liquid Layers - Schuschke, Christian; Hohner, Chantal; Stumm, Corinna; Kettner, Miroslav; Fromm, Lukas; Görling, Andreas; Libuda, Jörg (Journal of Physical Chemistry C, 2019)
Solid catalysts with ionic liquid layers (SCILLs) have recently attracted a lot of attention, as the ionic liquid (IL) coating can give rise to drastically improved selectivity. Here, we studied the interaction of the IL 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)-imide [C4C1Pyr][NTf2] with Pt(111) and Pt nanoparticles (NPs) on highly oriented pyrolytic graphite under ultrahigh vacuum conditions. The IL film on Pt(111) and on the Pt NPs consists of a strongly bound monolayer and a weakly bound bulk phase. In the monolayer, [NTf2]- adopts cis conformation and binds via the SO2 groups. Adsorption of [NTf2]- at Pt defect sites is preferred to adsorption at terraces, whereas preadsorbed CO blocks the adsorption at defects. Further, IL coadsorption leads to desorption and displacement of on-top CO on terraces, whereas CO resides in the bridging position. IL multilayers desorb at 380 K, whereas the strongly adsorbed monolayer on Pt resides and gradually desorbs and decomposes between 400 and 500 K. Finally, we studied the permeability of IL layers for CO by pressure modulation experiments in combination with in situ infrared reflection absorption spectroscopy. We show that the IL multilayer completely blocks CO adsorption, whereas CO easily penetrates the IL monolayer film and forms a mixed adsorbate phase. It is noteworthy that dynamic CO adsorption is much more facile on Pt NPs than on Pt(111). Our results suggest that strongly adsorbed IL monolayers may play an important role in real SCILLs.
CRIS-Team Scopus Importer:2019-12-31